PERSEPSI ORANG TUA TENTANG PERKEMBANGAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN (PENELITIAN SURVEI DI TAMAN KANAK-KANAK (TK) WILAYAH GUGUS III KECAMATAN CIBINONG, KABUPATEN BOGOR) - Sabillah, El; Hapidin, Hapidin; Syamsiatin, Eriva (Al Hanin, 2021)
This experiment was intended to describeparents perception about early reading development of children 5-6 years old. The sample of this experiment was 100parents at Kindergarten in Gugus III area In The District of Cibinong, Bogor. The technique of getting sample was quota sampling. Data were collected throught questionnaire. The results of the study of parents' perceptions of the development of early reading of children aged 5-6 years by 76% are in the category of "good" and as much as 24% in the category of "enough". In a more specific description, the perception of parents has several sub-aspects. In the sub- aspect of the meaning of early reading development of children aged 5-6 years the results show that 77% of parents are in the "good" category, and 23% of parents are in the moderate category. In the sub-aspects of the characteristics of early reading development of children aged 5-6 years the results show that 46% of parents are in the "good" category, and 54% of parents are in the "sufficient" category. In the sub-aspects of the aspects of early reading development of children aged 5-6 years, the results showed that 62% of parents were in the "good" category, and 38% were in the "sufficient" category. In the sub-aspects of parental strategies in developing early reading development of children aged 5-6 years, the results show that 77% of parents are in the "good" category and 23% of parents are in the moderate category.